The Folkstories of Children - Sutton-Smith, Brian (Book collections on Project MUSE., 1981)
The Folkstories of Children, first published in 1981, features nearly five hundred stories that were volunteered by fifty children between the ages of two and ten and transcribed word for word. The stories are organized chronologically by age of the teller, revealing the progression of the children's cognition and verbal competence.